Effect of different C/N ratios of biofloc technology in the growth of Pacific white shrimp (Litopenaeus vannamei) juvenile production, quantity of floc, and total ammonia nitrogen (TAN) level of the culture system - Figueroa, Jerian Dale Verdejo (2016.)
This study evaluated the effect of different C/N ratios of the BFT culture system on the growth of juvenile L. vannamei, quantity of produced floc, and in the ammonia level of the culture medium. Triplicate set-ups of culture systems were utilized and maintained at varying C/N ratios (8, 12, 16). Control (C/N 0) set-ups were established by the absence of molasses. 40 juvenile shrimps were stocked per tank with a water holding capacity of 80 L. Different amount of molasses was added at a daily basis to maintain the experimental treatments and to assess its effects. At the end of experiment, results showed that maintaining the C/N ratio at different levels does not cause a significant difference (p > 0.05) in the growth parameters of L. vannamei. In terms of ammonia reduction, C/N 16 yielded the lowest ammonia value with 0.36(±0.255) ppm at the final week. The density of biofloc is also affected with the change in C/N ratio. C/N 0 and 16 produced the highest level with 10.5±2 and 11.5±1.8 respectively. The overall results suggest that C/N ratio tends to affect the environmental conditions of the culture system; however, it may not have a direct effect on the growth of L. vannamei.
Thesis (Undergraduate, Bachelor of Science in Fisheries) Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas. 2016.
Keywords: Biofloc technology; Pacific white shrimp; Litopenaeus vannamei; Total Ammonia Nitrogen (TAN).